2016
DOI: 10.1080/20469047.2015.1106079
|View full text |Cite
|
Sign up to set email alerts
|

Severe malnutrition in children in Papua New Guinea: effect of a multi-faceted intervention to improve quality of care and nutritional outcomes

Abstract: Implementation of a multi-faceted intervention to improve the management of children with severe malnutrition was associated with improved quality of care and improved weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…The World Health Organization (WHO) guidelines for the management of SAM have been shown to be demonstrably effective when implemented appropriately [ 2 , 7 - 9 ], and well-trained, motivated staff have been shown to reduce SAM mortality in practice [ 9 - 11 ]. It has been suggested that by harnessing the potential of technology, particularly the internet, it should be possible to train health professionals at scale [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) guidelines for the management of SAM have been shown to be demonstrably effective when implemented appropriately [ 2 , 7 - 9 ], and well-trained, motivated staff have been shown to reduce SAM mortality in practice [ 9 - 11 ]. It has been suggested that by harnessing the potential of technology, particularly the internet, it should be possible to train health professionals at scale [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the case fatality rate fell from 5.8% preintervention to 1.9%, even though participating hospitals managed more SAM children themselves postintervention instead of transferring them to tertiary hospitals for treatment. In-service face-to-face training has been shown to benefit quality of care and case-fatality in severely malnourished children11–13 but as far as we are aware this is the first time that an eLearning course has been evaluated and found to be effective in improving the identification, clinical management, and survival of children with SAM. This is important because it demonstrates that the eLearning course can scale up the training of health professionals in the management of SAM, which is identified as the key to substantially decreasing case-fatality rates worldwide 14.…”
Section: Discussionmentioning
confidence: 97%
“…The WHO guidelines for the management of SAM have been shown to be demonstrably effective when implemented appropriately [2,[21][22][23] and well trained, motivated staff have been shown to reduce SAM mortality in practice [23][24][25]. These studies, which illustrate the efficacy of the WHO guidelines in reducing child mortality and improving recovery, also highlight the importance of 'motivated' and 'skilled' staff who follow the WHO Ten Steps with fidelity, and optimize the impact on clinical outcomes.…”
Section: Previous Findingsmentioning
confidence: 97%